2010
DOI: 10.1002/ajmg.b.31025
|View full text |Cite
|
Sign up to set email alerts
|

Significant association between the C(−1019)G functional polymorphism of the HTR1A gene and impulsivity

Abstract: Serotonin-1A (5-HT(1A)) receptors are known to play a role in impulsivity-related behavior. The C(-1019)G functional polymorphism (rs6295) has been suggested to regulate the 5-HT(1A) receptor gene (HTR(1A)) expression in presynaptic raphe neurons, namely, increased receptor concentration and reduced neuronal firing could be associated with the G allele. Previous studies indicate that this polymorphism is associated with aggression, suicide, and several psychiatric disorders, yet its association with impulsivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 65 publications
1
35
0
1
Order By: Relevance
“…In subjects with personality disorders, the Gallele was associated with emotional-dramatic behavior [128]. In normal subjects the GGgenotype has been found to confer an increase in impulsivity [129], as well as with neuroticism [130], although the latter has not been replicated [131]. However, no association with anxiety or depression personality traits was detected in a large study of healthy subjects [132], suggesting that these associations may be most robust in patients compared to normal subjects.…”
Section: -Ht1a Promoter Polymorphisms and Mental Illnessmentioning
confidence: 99%
“…In subjects with personality disorders, the Gallele was associated with emotional-dramatic behavior [128]. In normal subjects the GGgenotype has been found to confer an increase in impulsivity [129], as well as with neuroticism [130], although the latter has not been replicated [131]. However, no association with anxiety or depression personality traits was detected in a large study of healthy subjects [132], suggesting that these associations may be most robust in patients compared to normal subjects.…”
Section: -Ht1a Promoter Polymorphisms and Mental Illnessmentioning
confidence: 99%
“…. LL impulsivity [82] n ¼ sample [97]. The serotonin receptor 1B gene (HTR1B) is located with several mouse alcohol QTLs on chromosome 9, and geneknockout studies performed in mice implicated the HTR1B gene in both alcohol preference and aggression [98,99].…”
Section: Genes Influencing Impulsivitymentioning
confidence: 99%
“…It has been shown that the G allele and the G/G genotype of the common functional polymorphism -1019C>G (rs6295) in the human 5-HT1A receptor gene (HTR1A) could be associated with an increased risk of suicidal and impulsive behavior [29,30].…”
Section: Doi: 101159/000487484mentioning
confidence: 99%